Developing AI-Enhanced Writing Materials for University Students: A Case Study at Universitas Muhammadiyah Surakarta - Pamungkas, Damar Jati; Muamaroh, M; Ratih, Koesoemo; Hikmat, Mauly Halwat (Universitas Muhammadiyah Surakarta, 2025)
This study explores the development of Artificial Intelligence (AI)-enhanced teaching materials for improving university students' writing skills at Universitas Muhammadiyah Surakarta (UMS). In response to the ongoing digital transformation in higher education, AI-based tools such as Grammarly, ChatGPT, and Write & Improve have been increasingly utilized in writing instruction. The study employs a qualitative descriptive design and gathers data through classroom observations, semi-structured interviews with three English lecturers, and reflective journals from twenty students in the English Education Department. The findings reveal that AI tools significantly enhance students' engagement, critical thinking, and awareness of writing mechanics. However, several challenges remain, including over-reliance on AI, gaps in digital literacy, and insufficient teacher training. The study proposes a localized model for AI-integrated material development grounded in Tomlinson's (2011) materials development framework and the TPACK model (Mishra & Koehler, 2006). It concludes that thoughtful integration of AI can enrich the process writing approach and promote learner autonomy when pedagogical principles remain central to instructional design.